1999
DOI: 10.1146/annurev.publhealth.20.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Benefit Management Companies: Dimensions of Performance

Abstract: Research on pharmacy benefit management companies focuses on descriptive accounts of the organizations and the scope of their services. This review provides a critical analysis of publicly available research on contemporary issues surrounding the operations and effects of pharmacy benefit management companies. There has been very little systematic, empirical research on these issues; major questions concerning the impact of pharmacy benefit management companies on quality, costs, and patient outcomes remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The most significant difference between the 1999 Clinton proposal and the one considered in 1993–94 as part of the health security act was that participants would receive prescription drug benefits through existing health plans or through a regional pharmacy benefit manager operated by retail drug chains, health insurers, states, or other qualified entities and selected by Medicare through competitive bidding. By 1999, pharmacy benefit managers served about half of the insured population in the United States and performed the following functions: (1) claims processing and adjudication, (2) pharmacy network management, (3) formulary development and management, and (4) rebate negotiations and contracting with drug manufacturers (Copeland 1999; Lipton et al 1999). Unlike the earlier Clinton proposal, this one relied on the private sector's management and competition to control costs, not direct governmental regulation.…”
Section: Missed Opportunities For a Prescription Drug Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant difference between the 1999 Clinton proposal and the one considered in 1993–94 as part of the health security act was that participants would receive prescription drug benefits through existing health plans or through a regional pharmacy benefit manager operated by retail drug chains, health insurers, states, or other qualified entities and selected by Medicare through competitive bidding. By 1999, pharmacy benefit managers served about half of the insured population in the United States and performed the following functions: (1) claims processing and adjudication, (2) pharmacy network management, (3) formulary development and management, and (4) rebate negotiations and contracting with drug manufacturers (Copeland 1999; Lipton et al 1999). Unlike the earlier Clinton proposal, this one relied on the private sector's management and competition to control costs, not direct governmental regulation.…”
Section: Missed Opportunities For a Prescription Drug Benefitmentioning
confidence: 99%
“…Without this institutional development, policymakers ideologically inclined to rely on the private sector's administration would not have had any experience on which to judge the viability of this approach. As it is, there are few examples of stand‐alone drug plans that bear financial risk (CBO 2002), great uncertainty that insurers will actually participate in a Medicare drug benefit program (Goldstein 2003a, d; Health Policy Alternatives 2003a), and little evidence to date that they can control the costs of a major new Medicare benefit (Lipton et al 1999; Lipton et al 2000). When serving as administrator of the Centers for Medicare & Medicaid Services, Thomas Scully contended in congressional testimony that stand‐alone drug coverage “does not exist in nature” and would probably not work in practice (Pear 2003e).…”
Section: Patterns In Policymaking and Their Consequences For Medicarementioning
confidence: 99%
“…These plans varied with respect to copayment ($5 or $10 per prescription), use of a drug formulary (yes or no), required use of mail-order pharmacy (yes or no), and monthly premium. Use of drug formularies and mail-order pharmacy programs were chosen as qualitative attributes, because they are used widely by PBMs (Lipton et al 1999). The first three attributes were assigned using an experimental design method (Taguchi 1988).…”
Section: Hypothetical Plan Design and Choice Taskmentioning
confidence: 99%
“…Moreover, Lipton et al [33] also reported how Pharmacy Benefit Managers exert their influence to change prescribing decisions on cost grounds. Thomas et al [31] retrospectively evaluated the impact on asthma control of steroid inhaler switching without an accompanying visit or consultation M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 in the UK.…”
Section: Switching Without Consultationmentioning
confidence: 99%